Effect of Hindered Phenol Crystallization on Properties of Organic Hybrid Damping Materials - Zhang, Lin (Materials (Basel), 2019)
Organic hybrid damping materials have achieved sustainable development in recent years for superior damping properties due to the hydrogen bonding of hindered phenol. However, the aggregation and crystallization of hindered phenol in the matrix can lead to a sharp decline in material properties. Thus, a series of hindered phenol hybrid carboxylated nitrile rubber (XNBR) composites with different types and contents of hindered phenol were prepared by melt blending to study the effects of different hindered phenol on the properties of organic hybrid damping materials. A dynamic mechanical analyzer (DMA) and scanning electron microscope (SEM) were used to study the dynamic mechanical properties and cross-section morphology of composites. X-ray diffraction (XRD) was used to study the crystallization of hindered phenol. The results show that the properties of organic hybrid damping materials were affected by the structure of hindered phenol, and that hindered phenol molecules with a linear structure had better performances. The greater the number of hydrogen bonds between hindered phenol and the XNBR matrix, the more difficult it was for the hindered phenol to crystallize.